PERAN KEGIATAN EKSTRAKURIKULER DALAM PEMBENTUKAN KARAKTER SISWA DI SMAS ALWASHLIYAH TANJUNG MORAWA - M Padeli Wibowo; Indri Febrianti; Nanjah Fachira Ayundari (Cemara Education and Science, 2024)
The focus of the problem in this research is to cover the influence of extracurricular activities and character that can be developed through extracurricular activities at SMAS Al Washliyah Tanjung Morawa. This research aims to determine the influence of extracurricular activities at SMAS Al Washliyah Tanjung Morawa on the formation of student character and what characters can be developed through extracurricular activities in the school environment. This research was carried out using a qualitative approach as a methodological framework. A qualitative approach was chosen to deepen understanding of the observed phenomena, explore subjective aspects, and explore meaning from participant perspectives. This method allows researchers to understand the context, relationships and dynamics that arise in the research context. Based on the research results, information related to how extracurricular activities can influence the formation of student character at SMAS Al Washliyah Tanjung Morawa, highlights the importance of extracurricular activities in forming student character. The Ministry of Education and Culture pays special attention to character education, and extracurricular activities in schools are a forum for developing students' character. Information related to character that can be developed through extracurricular activities in the school environment, especially at SMAS Al Washliyah Tanjung Morawa. It can be concluded that extracurricular activities play a role which is very significant in shaping student character. This research shows that participation in extracurricular activities has a real positive impact on various aspects of students' character development. Students who are active in extracurricular activities show an increase in their talents and interests, which has an impact on increasing self-confidence and motivation to learn